If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2/3)*x-(3/2) = -1/5 // + -1/5
(2/3)*x-(3/2)-(-1/5) = 0
(2/3)*x-3/2+1/5 = 0
2/3*x-13/10 = 0 // + 13/10
2/3*x = 13/10 // : 2/3
x = 13/10/2/3
x = 39/20
x = 39/20
| g=77-22 | | 3x-7=6x-4 | | 4x+8=16-2x | | 2a^2-3=-5a | | x+36=2x+8 | | 4b+8=16-2x | | 13x-1=4(3x+3)-11 | | 2(3x+7)=-44+4 | | 7k^2=5-34k | | m-3+13=20 | | 2x-3=2x+2 | | 5n^2-40n=0 | | g+48=54 | | 6y+6=2y+8 | | 9-4x=2x-3 | | 45/4m=35/3 | | f=53-24 | | 5k^2+20k=-15 | | ln(x)+ln(2x)=0 | | 52y-3.1=12 | | 19(v+4)-3v=4(4v+4)-24 | | 5x6/15-2 | | 2-x=2x-6 | | 3m^2-6m=9 | | 4.5(x+5.5)=4.5(x+5.5) | | 13t+10=-3 | | 5t+6=26 | | x^3=6x+x^2 | | 26+3y-3=15y-12-5y | | 5a-10=-5a | | 6v^2+252=78v | | 12y+164=7.6 |